Italy : Financial Sector Assessment Program-Technical Note-Systemic Risk Oversight Framework and Macroprudential Policy. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Macroprudential oversight in Italy combines local elements with the European framework. At a local level, financial stability is a shared responsibility between Banca d'Italia (BdI), which is the national central bank and the prudential authority for banks and other financial institutions, the markets authority, Commissione Nazionale per le Societa e la Borsa (CONSOB), the insurance supervisor, Istituto per la Vigilanza Sulle Assicurazioni (IVASS), and the pension funds supervisor, Commissione di Vigilanza sui Fondi Pensione (COVIP).2 Each authority exercises its responsibility within a combination of sectoral and activity boundaries and the BdI plays a leading role in surveillance and coordination. Within the European framework, the BdI is both the national competent authority and the designated authority for the macroprudential tools considered under the Capital Requirements Regulation (CRR) and the Capital Requirements Directive IV (CRD IV), which are implemented and activated following the processes described in these regulatory texts and the guidelines provided by the European Central Bank (ECB) - within the competences assigned to it by the SSM Regulation - and the European Systemic Risk Board (ESRB). The ubiquitous role of the BdI on both fronts eases the challenges posed by the coexistence of these two frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet